A case study on the implementation of design in advertising muslimah salon Malaysia / Nur Liyana Azlan - Azlan, Nur Liyana (Faculty of Art and Design, 2015)
In the modern world, women are very concerned about their hair is considered a crown. Therefore, a beauty center called the salon is a place for them to make beauty treatments from hair to toe. There are many salon around us. But for Muslim women they will go to the salon concept salon Muslims only. Salon Muslims in Malaysia is not new anymore but it has long been established here and has many sprouting like mushrooms after the rain. What are meant by the implementation of the design is a matter of such elements associated with a particular work. In this research, advertising as the main priority will be reviewed. So, regarding to this topic are actually to investigate about what are the elements of design that are suitable for muslim women. This research are important to know what is the most suitable design that implementable towards advertising about muslimah salon. Elements of design will be studied for know more about it. We see that advertising often related to posters and others. In order to promote a service, many things and elements that need to be studied and known before doing so. Among the things that should be emphasized is the design elements such as line, shape, form, color and others. Not all of these elements should be included in a Muslim women concept of advertising. Thus, this study will be carried out by a number of salons advertising that already in the market to be compared in order to facilitate this study. This study will not take out the relevant services and their management, but instead just put the design sheer only.